Etude comparative de la qualité des eaux du Complexe terminal et du Continental Intercalaire aux fins d’utilisation mixte AEP-irrigation dans la zone d’Oued-Righ - رحال, محمد المهدي; بالعيد, العربي (University of El Oued جامة الوادي, 2018)
يتناول هذا العمل مشكلة نوعية المياه في خزانات المياه الجوفية لشركة C.T و C.I في منطقة Oued-Righ لاستخدامها في تغذية الإنسان والري. لهذا ، فإن تظهر النتائج التي تم الحصول عليها أن مياه Albian مقبولة إلى حد ما للشرب في حين أن من C.T فقيرة وتتطلب العلاج. أما بالنسبة لاستخدامها في الحقل الزراعي، فإن C.T هو الأكثر معتبرا في الاعتبار المحتويات التي تقدر بتسميد العناصر على وجه الخصوص من النيتروجين والفوسفور. يجب أن مياه C.I تكون مبردة سابقا والعلاجات ضرورية لمياه هذه الطبقات المائية في من أجل تصحيح المستويات العالية للعناصر الكيميائية والفيزيائية المختلفة. أخيرا ، يجب أن نحل مشاكل العدوانية ، الصلابة العالية ، التدرج ، الخ ... ، لجعل هذه المياه معيارية نوعيا. This work deals with the water quality problem of the underground aquifers of C.T and C.I in the Oued-Righ region for use in human nutrition and irrigation. For this, the results obtained show that Albian waters are more or less acceptable for drinking while that of the C.T are poor and require treatment. As for their use in the agricultural field, the C.T is most indicated considering the appreciable contents of the fertilizing elements in particular of nitrogen and phosphorus. The waters of C.I must be previously cooled and treatments are essential for the waters of these aquifers in order to correct the high levels of the different chemical and physical elements. Finally we must solve the problems of aggressiveness, high hardness, scaling, etc ..., to make these waters qualitatively normative.
مذكرة ماستر ري تخصص تشخيص وتصميم أنظمة الري و المياه المستعملة
Keywords: Underground tablecloths - continental intercalary - terminal complex - aggressiveness - hardness - mineralization; الطبقة الجوفية - الطبقة الاخيرة C.I - الطبقة الثانية C.T - عدوانية - ثقل - تمعدن